Peningkatan Kemampuan Membaca Permulaan Melalui Permainan Huruf dan Kata dengan Menggunakan Gaya Belajar Visual, Auditori dan Kinestetik - Erna Olua (Universitas Lampung, 2019)
The purpose of this research was to describe the implementation process play letter and word and to understand improving early reading ability of children in group B1 through play letter and word. The study was conducted on group B Kindergarten with of fiftten children. This study used action research methods by Kemmis and Taggart which consist of 4 stages (plan, action, observation and reflection). This study consisted of two cycles, each cycles consisting of 8 sessions. Data collecting techniques used observation, field notes and documentation. Data analysis using quantitative and qualitative data. Quantitative data analysis with descriptive statistics that compare the result obtained from the first cycle and the second cycle. Analysis of qualitative data by analizing data from the observation, fields notes and documentation during the study to the steps of data reduction, data display and data verification. The result of this study showed that there was the improving early reading ability through play letter and word using learning style visual, auditory and kinesthetic with score in pre cycle 34,8 had improvement to 51,4 and become 63,5 in cycle II and excellent growing categoryKeywords: early reading ability, playing letter and word, learning style visual, auditory and kinestheticDOI: http://dx.doi.org/10.23960/jiip.v1i1.18007